Photurgen: The open source software for the analysis and design of hybrid solar wind energy systems in the Caribbean region: A brief introduction to its development policy. (November 2017) - Watson, Daren; Binnie, Yekini; Duncan, Keith; Dorville, Jean-Francois
Abstract: Hybrid Renewable Energy Systems (HRES) use multiple renewable resources such as hydro, solar and wind collaboratively to produce energy that can meet a defined load demand continuously. Their combination can lead to the improvement in the systems efficiency and overall reliability. However, the level of penetration of HRES in the Caribbean region is less than its expected potential. The constraints generated by their complexity and the costly access to useful energy planning tools is a limitation to their implementation. Therefore, in collaboration with the Alternative Energy Research Group, UWI Mona, we develop a free Linear Optimization software, Photurgen, for the design and analysis of hybrid solar-wind systems within the Caribbean region. Solar-wind hybrid systems are simulated based on historic climatological resources and instantaneous load consumption data, providing the user with graphics and advice for their optimal configuration. This paper introduces the first version of Photurgen and its associated development policies. This tool is one simple solution to be applied to increase the rate of autonomous and grid-tied households within the region, with Jamaica being its experimental location.